Large intrathoracic meningocele in a patient with neurofibromatosis type 1. (February 2014) - Zuo, Tao; Ni, Zhengyi; Zhou, Mi; Huang, Chaolin; Tang, Zhongwen; Yang, Zhifeng
Intrathoracic meningocele associated with neurofibromatosis type 1 is quite rare. We report the case of a Chinese women with a 20-day history of right-sided chest pain and sense of pressure on the chest. Computed tomography and magnetic resonance imaging indicated a homogeneous thin-walled cystic mass in the right rear mediastinum, ranging from the 1st to 5th thoracic segments. Surgery was performed to removal the meningomyelocele pouches and shunt the cyst to the subarachnoid region.